ECOLOGICAL ASPECTS OF THE WATER STRIDERS Charmatometra bakeri Kirkaldi (HETEROPTERA: GERRIDAE) IN THE VALLEY OF CAUCA - ASTUDILLO, ANA MILENA; GUTIÉRREZ, YOLANDA; MEDINA, CLAUDIA A.; MANZANO, MARÍA DEL R. (Revista Colombiana de Entomología, 1992)
The species C. bakeri was studied at 10 stations in the Bitaco river (Chicoral-La Cumbre, Valle; at 1970 m.a.s.I., in a very humidlower montane forest. It was found that C. bakeri is distributed in groups of nymphs and adults which are always in constant activity, and this allows them to remain in communication when the water is disturbed. They are sensitive to movements caused by the prey when falling into the water. Their diet is varied and is composed mainly of insects, mostly adults of Cercopidae (Homoptera) (31%) and ants (Hymenoptera: Formicidae) (27%). In the field, they oviposited mainly on partially submerged rocks and logs on the surface. In the laboratory, the eggs were deposited preferentially on pieces of wood. In the river, by marking individuals with vegetable markers, it was found that in the average they move upstream 214.6 m and downstream 168 m. Associated with C. bakeri were found the predatory species Dineutus sp. (Coleoptera: Gyrinidae) and Rhagovelia sp. (Hemiptera: Veliidae).